Model Tests on a 'Wind' Class Icebreaker for the United States Coast Guard. I - Dix, P. J. (1966)
The ability of the craft to break ice of greater thickness than that associated with continuous forward motion was assessed in a series of charging tests. The ice fields employed for this work were made up of a series of steps of increasing thickness so that each successive charge broke into stronger ice. Between experiments, the edge of the field was trimmed back into an unbroken line across the tank so as to ensure an absence of any effect which might remain from previous charges. The icebreaking ability of the craft was assessed for charging distance of 1.0, 2.0 and 3.0 shiplengths at the four power ratings of 10,000, 20,000, 30,000 and 40,000 S.H.P. In each case the maximum thickness which could be broken was defined as that into which the craft would enter for approximately 0.25 of a shiplength. See also AD-861 592L.